Second dictionary of acronyms & abbreviations : more abbreviations in management, technology and information science - Pugh, Eric.; Pugh, Eric. (London : Bingley, 1974)
This second volume contains another 10,000 entries. One explanation which covers both volumes is the word 'PRORAM' which is the accepted standard term relative to software in computer data processing. However, because of the variance in the usage of this word in the USA, the author used 'PROGRAMME' to cover data processing; 'PROGRAM' has only been used when it covers proceedings, or projects, undertaken by institutions, etc. in the USA.
"This book is a supplement to Eric Pugh's A dictionary of acronyms and abbreviations, second edition 1970."
Includes index.
ne 25/08/2021
Ref.
Keywords: Technology; Management; Information science; Acronyms